The Rosie project [large type] : a novel - Simsion, Graeme C. (Center Point Large Print, 2013)
Don Tillman, professor of genetics, has never been on a second date. He is a man who can count all his friends on the fingers of one hand, whose lifelong difficulty with social rituals has convinced him that he is simply not wired for romance. So when an acquaintance informs him that he would make a "wonderful" husband, his first reaction is shock. Yet he must concede to the statistical probability that there is someone for everyone, and he embarks upon The Wife Project. In the orderly, evidence-based manner with which he approaches all things, Don sets out to find the perfect partner. She will be punctual and logical -- most definitely not a barmaid, a smoker, a drinker, or a late-arriver . . . yet Rosie Jarman is all these things. She is also beguiling, fiery, intelligent -- and on a quest of her own. She is looking for her biological father, a search that a certain DNA expert might be able to help her with. Don's Wife Project takes a back burner to the Father Project and an unlikely relationship blooms, forcing the scientifically minded geneticist to confront the spontaneous whirlwind that is Rosie -- and the realization that love is not always what looks good on paper.